AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN MASJID DI KOTA BANDA ACEH - khairaturrahmi khairaturrahmi; Ridwan Ibrahim (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This study has purpose  to describe how accountability and transparancy in financial management at the mosques in Banda Aceh . This study is descriptive qualitative study. Data is collected by interview to mosques management in Banda Aceh . The primary data collected by interview is used in this study. The results of this study indicate that generally, the Mosques in Banda Aceh  were not fully implemented transprancy and accountability in its financial management